Handbook of Fuel Cells 2010
DOI: 10.1002/9780470974001.f500004
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal/polymer catalysts forO2reduction

Abstract: Transition metal/polymer catalysts for O 2 reduction have been investigated extensively as a less expensive, more abundant alternative to platinum catalysts for polymer electrolyte fuel cell (PEFC) cathodes. Embedding metals into polymers offers many potential advantages analogous to the function of metal‐containing enzymes, which include bringing the metal centers into proximity for cooperative action and moderating the local pH near the metal to improve catalyst stability. In this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Co-based catalysts of the type Co/N/C and catalysts based on Co and Fe (Co–Fe/N/C) have also shown interesting properties, even if, according to Figure , Co is a much less common metal than Fe. Several book chapters and review articles have already been written about Fe- and/or Co-based catalysts made to perform the oxygen reduction reaction (ORR) in fuel cells. , In this literature, it is also reported that, besides the non-noble metal-based catalysts, some metal-free catalysts made of carbon doped with several heteroatoms (the most common one being nitrogen) may also reduce O 2 electrochemically in acid medium. …”
Section: Carbon-based Non-noble Metal and Metal-free Catalystsmentioning
confidence: 99%
“…Co-based catalysts of the type Co/N/C and catalysts based on Co and Fe (Co–Fe/N/C) have also shown interesting properties, even if, according to Figure , Co is a much less common metal than Fe. Several book chapters and review articles have already been written about Fe- and/or Co-based catalysts made to perform the oxygen reduction reaction (ORR) in fuel cells. , In this literature, it is also reported that, besides the non-noble metal-based catalysts, some metal-free catalysts made of carbon doped with several heteroatoms (the most common one being nitrogen) may also reduce O 2 electrochemically in acid medium. …”
Section: Carbon-based Non-noble Metal and Metal-free Catalystsmentioning
confidence: 99%
“…Several recent literature reviews have demonstrated the importance of elucidating the ORR active sites in this class of catalyst. , This study is a follow-up on a previous effort in the development of PANI–Fe–C ORR catalyst at Los Alamos National Laboratory. , The purpose of the study was to elucidate the identity of the active site in the PANI–Fe–C class of catalysts by correlating ORR activity with the catalyst morphology and chemical speciation as a function of variation in the catalyst preparation procedure, specifically heat treatment temperature and presence of sulfur-containing precursor. The main technique utilized in this study was X-ray absorption fine structure (XAFS) spectroscopy, which comprises X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) and enables the measurement of atomic structure, bonding characteristics, and oxidation state with elemental specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was found that the pyrolysis products of these compounds, as well as other complexes obtained from Co and Fe salts, N-donor ligands and/or polymers, supported on different carbons displayed a higher activity and stability than their precursor materials, comparable in some cases to that of Platinum [16][17][18]. Recently, metal-free catalysts, consisting mainly in Ndoped carbons (graphenes, nanotubes, carbon nitride, etc) have shown ORR activity which was even higher than that of Platinum in alkaline medium [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Although catalysts for ORR have been synthetized for decades [13][14][15][16][17][18], there is still a big debate about the ORR active site for Ptfree catalyst [22,23]. Three main models of the structure of the active site have been proposed: i) Fe-N 4 or Co-N 4 moieties bound to the graphite structure during thermal treatment [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation